Factors associated with elevated serum IgG4 in rheumatic diseases - Juhua Dai; Xinping Sun; Ju Yang; Jie Zhang; Lianjie Shi (Medicine, 2026)
Elevated serum immunoglobulin G4 (IgG4) levels have been reported in various rheumatic diseases; however, the factors associated with IgG4 elevation remain incompletely understood. This study aimed to evaluate the frequency of elevated serum IgG4 in different rheumatic diseases and to explore its association with disease classification based on typical inflammatory characteristics and autoantibody status. This retrospective single-center study included 255 patients with rheumatic diseases who underwent serum IgG4 testing between January 2017 and December 2022. Patients were categorized for exploratory disease-level analyses according to their typical association with elevated C-reactive protein (CRP) levels (rheumatoid arthritis [RA], spondyloarthritis, vasculitis, and adult-onset Still disease) or without prominent CRP elevation (Sjögren syndrome, systemic lupus erythematosus, retroperitoneal fibrosis, idiopathic inflammatory myopathy, and undifferentiated connective tissue disease), as well as according to the presence or absence of disease-specific autoantibodies. The frequency of elevated serum IgG4 (≥1.35 g/L) was compared between groups. Elevated IgG4 was more frequently observed in patients with RA than in those with Sjögren syndrome (30.36% vs 11.83%, P = .005). Rheumatic diseases classified as CRP-associated demonstrated a higher frequency of elevated IgG4 than non-CRP-associated diseases (30.23% vs 14.20%, P < .001). Among patients with RA, elevated IgG4 was associated with higher levels of immunoglobulin M, immunoglobulin G, CRP, erythrocyte sedimentation rate, and Disease Activity Score 28-CRP scores (all P < .05). In this retrospective cohort, elevated serum IgG4 was more frequently observed in rheumatic diseases classified as CRP-associated than in non-CRP-associated diseases. No significant association was observed between elevated serum IgG4 frequency and autoantibody status. These findings demonstrate an association between disease classification based on typical inflammatory characteristics and the frequency of elevated serum IgG4; however, prospective studies incorporating patient-level inflammatory assessments are required to determine the clinical significance of this association.